The Optimal Number of Oocytes Retrieved From PCOS Patients Receiving IVF to Obtain Associated With Maximum Cumulative Live Birth Rate and Live Birth After Fresh Embryo Transfer - Jia, Rui; Liu, Yuanyuan; Jiang, Rulan; Zhu, Xuli; Zhou, Liang; Chen, Peipei; Cao, Mingya; Zhao, Zhiming (Frontiers in Endocrinology, 2022)
Aims: To determine the optimal number of oocytes retrieved so that patients with polycystic ovary syndrome (PCOS) receiving in vitro fertilization (IVF) can obtain the best cumulative live birth rate and effective live birth. Methods: Retrospective study including 1419 patients with PCOS who underwent the first IVF cycle in the Second Hospital of Hebei Medical University from January 2014 to December 2021. Multivariable regression analysis was performed to adjust for factors known to independently affect cumulative live birth aspiration. The number of oocytes retrieved to obtain the best cumulative live birth rate was explored through curve fitting and threshold effect analysis. The method of decision tree was used to explore the best number of oocytes retrieved to achieve live birth in the shortest time. Results: The number of oocytes retrieved was an independent protective factor for cumulative live birth rate (CLBR) (OR = 1.09, 95% CI:1.06, 1.12). When the number of oocytes retrieved was less than 15, the cumulative live birth increased by 16% with each increase in the number of oocytes retrieved (OR = 1.16, 95% CI: 1.11, 1.22); when the number of oocytes retrieved was more than 15, the cumulative live birth tended to be stable. Effective live birth was analyzed through classification decision tree. For patients younger than 35 years old, those with less than 6 oocytes and those with 7-16 oocytes had a similar proportion of live births with fresh embryo transfer but higher than 16 oocytes (53.7 vs 53.8% vs 18.4%). Patients younger than 35 years old had a higher proportion of live birth of fresh embryo transfer (53.7% vs 38.8%) in those with less than 6 oocytes retrieved, but the proportion of no live birth after used up all embryos was higher than the total patients (41.0% vs 20.4%). Conclusions: In PCOS patients younger than 35, high CLBR can be obtained when the number of oocytes retrieved was 15 or more. The number of oocytes retrieved 6-16 could achieve live birth in the shortest time.